PENERAPAN MODEL PEMBELAJARAN PREDICT-OBSERVE EXPLAIN (POE) SEBAGAI SOLUSI ALTERNATIF UNTUK MENINGKATKAN PEMAHAMAN KONSEP FISIKA SISWA PADA MATERI HUKUM NEWTON KELAS X SMA - Nurhasana Nurhasana; Zuhdi Ma’aruf; Dedi Irawan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : Understanding is the level of ability expected by someone in understanding the meaning of the concept. Understanding the concept is a very important part in the learning process. The purpose of this study is to find out that the application of the predict-observe explain (poe) learning model can be an alternative solution to improve students' understanding of physics concepts. This study uses a quasi-experimental research method with a "posttest only control group design" research design. The affordable population is all students of class X MIA MAN 3 Pekanbaru in the 2021/2022 academic year, totaling 144 students. The sample in this study amounted to 72 students consisting of class X MIA 2 as the control class which amounted to 36 students and X MIA 3 as the experimental class which amounted to 36 students. The instrument used is a test of understanding the concept of Newton's Law material. This test refers to 7 indicators of concept understanding according to Widodo. The test questions consist of 21 multiple choice questions and 4 essay questions. After the test, the data on the results of students' understanding of the concept will be presented with descriptive analysis and inferential analysis. This descriptive analysis is seen through the absorption of students. In this inferential analysis using three tests with the help of SPSS version 24, namely normality test, homogeneity test and hypothesis testing with non parametric Mann Whitney. The results showed that the experimental class students' conceptual understanding data by applying the POE learning model had a significant difference than the control class which only used conventional learning.Keywords: Concept Understanding, POE Learning Model, Experimental Method, Newton's Law